Long‐term changes to the frequency of occurrence of British moths are consistent with opposing and synergistic effects of climate and land‐use changes. Issue 4 (29th April 2014) - Fox, Richard; Oliver, Tom H.; Harrower, Colin; Parsons, Mark S.; Thomas, Chris D.; Roy, David B.; Pärt, Tomas
Summary Species' distributions are likely to be affected by a combination of environmental drivers. We used a data set of 11 million species occurrence records over the period 1970–2010 to assess changes in the frequency of occurrence of 673 macro‐moth species in Great Britain. Groups of species with different predicted sensitivities showed divergent trends, which we interpret in the context of land‐use and climatic changes. A diversity of responses was revealed: 260 moth species declined significantly, whereas 160 increased significantly. Overall, frequencies of occurrence declined, mirroring trends in less species‐rich, yet more intensively studied taxa. Geographically widespread species, which were predicted to be more sensitive to land use than to climate change, declined significantly in southern Britain, where the cover of urban and arable land has increased. Moths associated with low nitrogen and open environments (based on their larval host plant characteristics) declined most strongly, which is also consistent with a land‐use change explanation. Some moths that reach their northern (leading edge) range limit in southern Britain increased, whereas species restricted to northern Britain (trailing edge) declined significantly, consistent with a climate change explanation. Not all species of a given type behaved similarly, suggesting that complex interactions between species' attributes and different combinations of environmental drivers determine frequency of occurrence changes. Synthesis and applications. Our findings are consistent with large‐scale responses to climatic and land‐use changes, with some species increasing and others decreasing. We suggest that land‐use change (e.g. habitat loss, nitrogen deposition) and climate change are both major drivers of moth biodiversity change, acting independently and in combination. Importantly, the diverse responses revealed in this species‐rich taxon show that multifaceted conservation strategies are needed to minimize negative biodiversity impacts of multiple environmental changes. We suggest that habitat protection, management and ecological restoration can mitigate combined impacts of land‐use change and climate change by providing environments that are suitable for existing populations and also enable species to shift their ranges.